2020
DOI: 10.37669/milliegitim.787933
|View full text |Cite
|
Sign up to set email alerts
|

Uzaktan Eği̇ti̇m Süreci̇nde Fen Bi̇li̇mleri̇ Dersi̇nde Deney Yapmaya İli̇şki̇n Öğretmen Görüşleri̇ni̇n Araştirilmasi

Abstract: Tüm dünyayı etkileyen Covid-19 salgını sonrası sınıflarda yüz yüze eğitim yerine internet ve TV üzerinden uzaktan eğitim gerçekleştirilmiştir. Fen derslerinin ayrılmaz bir parçası olan deney yapma uzaktan eğitim sürecinde nasıl gerçekleştirildiği araştırılması gereken bir nokta olarak karşımıza çıkmaktadır. Bu çalışma ile uzaktan eğitim sürecinde fen bilimleri dersinde deney yapmaya yönelik öğretmen görüşlerinin araştırılması amaçlanmıştır. Çalışma 34 fen bilimleri öğretmeni ile yürütülmüştür. Öğretmenlere uza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…This result is similar to the result of the study. In addition, similar results were obtained in the literature (Aksoy, Bozkurt, & Kurşun, 2021;Altuntaş Yılmaz, 2020;Bostan Sarıoğlan, et al, 2020;Jeffery & Bauer, 2020;Kaumba, Mphahlele, Muleya & Simui, 2021;Önal & Özdemir, 2021;Petillion & McNeil, 2020;Sandi-Urena, 2020;Şenyuva, 2007;Van Heuvelen, Daub & Ryswyk, 2020).…”
Section: Conclusion and Suggestionssupporting
confidence: 83%
See 1 more Smart Citation
“…This result is similar to the result of the study. In addition, similar results were obtained in the literature (Aksoy, Bozkurt, & Kurşun, 2021;Altuntaş Yılmaz, 2020;Bostan Sarıoğlan, et al, 2020;Jeffery & Bauer, 2020;Kaumba, Mphahlele, Muleya & Simui, 2021;Önal & Özdemir, 2021;Petillion & McNeil, 2020;Sandi-Urena, 2020;Şenyuva, 2007;Van Heuvelen, Daub & Ryswyk, 2020).…”
Section: Conclusion and Suggestionssupporting
confidence: 83%
“…In some studies examining the problems of distance education, they state that due to the lack of active interaction in distance education, it restricts the socialization of the individual students who do not know technology have difficulties in learning. Moreover, there are problems in teaching some practical courses through distance education, students are overburdened with responsibility and inequalities in access to education are revealed (Altıparmak et al, 2011;Altuntaş Yılmaz, 2020;Anderson, 2020;Bayram et al, 2019;Bostan Sarıoğlan et al, 2020;Can, 2020;Horzum, 2003;Usta et al, 2016). Rapanta et al, (2020) states that it is necessary to make the courses simpler and to reduce the expectations from the students in order to decrease their anxiety level while heading emergency remote education during COVID-19 Pandemics.…”
Section: Literaturementioning
confidence: 99%
“…& Aksoy, 2021), sınıf yönetimi (Kandemir & Sezgin Nartgün, 2022;Küçüker & Dernek Uzun, 2022), sosyalleşememe (Taşkın. & Aksoy, 2021), uygulamaya dönük becerilerin öğretilememesi (Karaevli & Levent, 2022;Kırıkçı, Arıkan & Çetin, 2022;Bostan Sarıoğlan, Altaş, & Şen, 2020;Dilman, 2022), veliler ile iletişim (Küçüker & Dernek Uzun, 2022) gibi konularında sorunlar yaşanıldığı tespit edilmiştir. Araştırmalarda yaşanılan sorunların sürecin önemli bir ögesi olan öğretmenlerin motivasyonlarını düşüren bir unsur olarak yer aldığına vurgu yapılmıştır (Orhan& Demir 2022).…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Can (2020) also states that the MNE should improve the infrastructure of distance education and turn it into a more effective alternative that is safe and easy to access. Some researchers have focused on distance education (Özgül et al, 2020;Bostan Sarıoğlan et al, 2020;Demir & Özdaş, 2020;Telli Yamamoto & Altun, 2020;Balaman & Hanbay Tiryaki, 2021). Alper (2020) concentrated on private school teachers' views of distance education and found that they could adapt to distance education and technology use.…”
Section: The Challenges Of Distance Education and Related Literaturementioning
confidence: 99%